Recycling awareness among undergraduate student under KAED environmental education: a case study of KAED’s students recycling behaviour - Elsawahli, Hanan Mohamed Hassan; Mohit, Mohammad Abdul (2010)
The combination of the Muslims practices of conservation and the environmental education in KAED ensured the recycling awareness of the students in the faculty. Recycling awareness among students helps in cleaning up the environment and participating in the daily natural life cycle to achieve sustainability. The amount of waste carried out of the studio step in the faculty everyday could be a real problem. Students work in the studio most of the time, everyone comes with food and drinks plus the paper used for the projects and model making. The purpose of the research was to analyze the relationship between the recycling awareness of the students and the environmental education they undertake in KAED. The study examined the differences in recycling awareness among the students of KAED and focused towards the students’ recycling awareness in relation to the year of study and the environmental studies they undertake. Chi-square and correlation were calculated for the data to determine the difference in recycling awareness among students in different years of study with respect to gender, department, attitude, facilities location and recycling knowledge undertaken in the faculty. The findings showed that the students’ recycling awareness is significantly related to the year of study. Gender and department showed no relation with the recycling awareness of the students. The results also showed that facilities location played an important part on awareness. Recommendations included intensifying the environmental educational programs to plan for more sustainable environments and increasing the number of recycling bins for better accessibility. Future studies are recommended to focus on the enhancement of the environmentally friendly behavior with respect to sustainable development.